2012
DOI: 10.1371/journal.pone.0034295
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic αVβ3 Integrin Inhibits Neurite Outgrowth and Promotes Retraction of Neuronal Processes by Clustering Thy-1

Abstract: Thy-1 is a membrane glycoprotein suggested to stabilize or inhibit growth of neuronal processes. However, its precise function has remained obscure, because its endogenous ligand is unknown. We previously showed that Thy-1 binds directly to αVβ3 integrin in trans eliciting responses in astrocytes. Nonetheless, whether αVβ3 integrin might also serve as a Thy-1-ligand triggering a neuronal response has not been explored. Thus, utilizing primary neurons and a neuron-derived cell line CAD, Thy-1-mediated effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 51 publications
2
71
0
Order By: Relevance
“…We also found that blocking THY-1 inhibited virus-induced activation of PI3K/Akt. THY-1 is known to interact with integrins (47)(48)(49)(50) and is a major protein present in clathrin-independent endocytic vesicles (39). Since macropinocytosis is PI3K/Akt dependent, involves integrin signaling, and is a clathrin-independent endocytic process, we determined whether THY-1 has a role in HCMV entry by macropinocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that blocking THY-1 inhibited virus-induced activation of PI3K/Akt. THY-1 is known to interact with integrins (47)(48)(49)(50) and is a major protein present in clathrin-independent endocytic vesicles (39). Since macropinocytosis is PI3K/Akt dependent, involves integrin signaling, and is a clathrin-independent endocytic process, we determined whether THY-1 has a role in HCMV entry by macropinocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…An α v β 3 integrin has been reported to bind to Thy-1 and trigger clustering of Thy-1, inactivation of Src, and neurite outgrowth inhibition (Herrera-Molina et al 2012 ). The complete fl ow of signaling events initiated as a consequence of Thy-1 integrin interactions awaits further investigation.…”
Section: Role Of Thy-1 In Neurobiologymentioning
confidence: 99%
“…Indeed, recently published studies reported that the α v β 3 integrin serves as a ligand for Thy-1 in neurons, which upon binding induces Thy-1 to aggregate in the plasma membrane and leads to neurite outgrowth inhibition and retraction of already formed processes (Herrera-Molina et al 2012 ). Astrocytes expressing α v β 3 , but not those in which the β 3 subunit has been reduced by specifi c siRNA, inhibit neurite growth of primary cortical neurons maintained for 4-7 days in culture.…”
Section: Neuronal Thy-1 and Its Interactions With Astrocytesmentioning
confidence: 99%
“…Integrin binding to neuronal Thy-1 results in the activation of astrocytes. In turn, the astrocyte integrin induces clustering of neuronal Thy-1, thereby leading to the inhibition of neurite outgrowth and to the retraction of neuronal processes [81]. This bi-directional astrocyte-neuron communication via integrins might play an important role in the process of axon repair following neuronal damage.…”
Section: Integrins In the Central Nervous Systemmentioning
confidence: 99%